Jesus Revolution: Pendekatan Refleksi Teologi Terhadap Media Film Sebagai Bentuk Penginjilan Kaum Muda di Society 5.0 - Darmadi, Daud; Buniarto Putri , Anita; Berta , Tamara (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2023)
Society 5.0 has develop many aspects of human life, one of which is the use of social media and the media contained therein. The church in its evangelization is experiencing new challenges to be able to adapt to current developments. Films are considered to be one of the evangelical media that can reach young people, judging by the high interest of young people in spending time in front of the screen. Jesus Revolution is a Christian film released in 2023, and this research will analyze how this film can be used as a medium for young people evangelism in Society 5.0. This research uses qualitative research methods with a theological reflection approach by Gordon Lynch. The data used includes primary and secondary data collected through literature study and analyzed using a narrative approach. The results of this research show that Jesus Revolution brings many Christian values ​​that are relevant to today's youth cultural issues, thus can be used as a media for evangelism in the Society 5.0 era.